A biased coin up-and-down sequential allocation trial to determine the ED90 of intrathecal sufentanil combined with ropivacaine 2.5 mg for labor analgesia - Yin, Qiaoli; Yu, Bin; Hao, Hua; Li, Gang; Sun, Junyan; Kong, Hao; Deng, Liqin (Frontiers in Medicine, 2024)
Purpose To determine the 90 percent effective dose (ED90) of intrathecal sufentanil combined with ropivacaine 2.5 mg for labor analgesia and observe its safety for parturients and neonates. Methods We conducted a prospective, double-blind, biased coin up-and-down study. We injected a fixed 2.5 mg ropivacaine combined with a designated dose of sufentanil intrathecally to observe the labor analgesic effect. The initial dose of sufentanil was assigned 1.0 μg, and the remaining doses were assigned as per the biased coin up-and-down method. The criterion of successful response was defined as VAS ≤ 30 mm after intrathecal injection at 10 min. Safety was evaluated in terms of maternal and neonatal outcomes. Results The ED90 dose of intrathecal sufentanil combined with ropivacaine 2.5 mg (0.1%, 2.5 mL) was 2.61 μg (95% CI, 2.44 to 2.70 μg) by isotonic regression. No respiratory depression, hypotension, or motor block was observed. Thirty-one (77.5%) parturients complained of pruritus, and 14 (35.0%) suffered nausea and vomiting. Three neonates reported a 1 min Apgar score of ≤7, and none reported a 5 min Apgar score of ≤7. Conclusion The ED90 of intrathecal sufentanil combined with ropivacaine 2.5 mg for labor analgesia was 2.61 μg. The dose is safe for parturients and neonates.